2022
DOI: 10.4236/fns.2022.137048
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Juice Production in Abomey-Calavi and Cotonou Municipalities (Benin): Socio-Professional Profile of Actors and Adoption Level of Hygienic Practices of Enterprises

Abstract: Fruit juice production sector is developing in Benin's major cities and appears to have both organisational and technical shortcomings. This study aimed to 1) establish the socio-professional profile of actors in the fruit juice production sector in Abomey-Calavi and Cotonou municipalities and 2) evaluate the adoption level of hygienic practices of enterprises. The methodological approach adopted in this study combined a semi-structured survey with direct observations in fifty enterprises. The statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This study was conducted from November 2020 to February 2021. Fifty (50) fruit juice enterprises previously identified by Noumavo et al (2022) were involved in the present study. These included semiindustrial (05) and artisanal (45) enterprises.…”
Section: Diversity Evaluation Of Fruit Juicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted from November 2020 to February 2021. Fifty (50) fruit juice enterprises previously identified by Noumavo et al (2022) were involved in the present study. These included semiindustrial (05) and artisanal (45) enterprises.…”
Section: Diversity Evaluation Of Fruit Juicesmentioning
confidence: 99%
“…Indeed, fruit juice is a nutritious drink that not only contains vitamins, minerals, proteins and protective antioxidants, but also provides an additional source of water (Heyman and Abrams, 2017). Noumavo et al (2022) showed that the fruit juice production sector is growing rapidly in southern Benin. It creates huge employment and generates significant income for the actors in the sector.…”
Section: Introductionmentioning
confidence: 99%
“…The pineapple juice market in Africa is growing and the Republic of Benin is no exception to this dynamic. The pineapple juice sector in Benin allows the creation of new economic activities that create jobs and therefore the fight against unemployment" [3].…”
Section: Introductionmentioning
confidence: 99%